Ethno-pornography sexuality, colonialism, and archival knowledge - Sigal, Peter Herman 1964-; Tortorici, Zeb 1978-; Whitehead, Neil L. (Duke University Press, 2020)
"ETHNOPORNOGRAPHY collects essays that both develop and critique the concept that gives the book its name. Ethnopornography, a term first coined by British anthropologist Walter Roth in the late nineteenth century, refers to the often eroticized observation--for supposedly scientific or academic purposes--of those deemed "other" by the observer. In Roth's case, he was concerned that the descriptions and images he recorded of the bodily and sexual practices of the Aboriginal people he studied were inappropriate for lay readers who might find them vulgar--or worse, titillating. The editors of this collection focus on what it is that creates the slippage between the pornographic and the scientific. In particular, they attend to the importance of race within the colonially created and maintained worlds of both research--ethnography in particular--and pornography. The essays cover time periods ranging from the sixteenth century to the present day, locations from West Africa to the United States, and topics from the literary casting of Islamic culture as sexually excessive and deviant by the Ottomans to a personal account of racially and colonially inflected tensions stemming from an anthropologist's sexual activities while in the field"--
Keywords: Racial Groups; Ethnologie; Race; Vie sexuelle; Ethnology; Sex customs; Sex; Sex -- Anthropological aspects; Sex -- Anthropological aspects -- History; Kolonialismus; Sexualisierung; Pornografie; Rassentheorie; Electronic books; History; Konferenzschrift -- 2006 -- Durham, NC